Characterization of Cell Wall Microstructure and Damage Behavior of Alloyed Aluminum Foam via Synchrotron‐Based Microtomography1. Issue 3 (19th October 2012) - Zhang, Qiang; Toda, Hiroyuki; Kobayashi, Masakazu; Uesugi, Kentaro; Suzuki, Yoshio; Hur, Bo‐Young; Kim, Seung‐Eun; Banhart, John; Moreno, Francisco García
Abstract The internal microstructure of the high strength Al–Zn–Mg foam was characterized via the synchrotron‐based X‐ray microtomography. Using three‐dimensional (3D) quantitative image analysis of the tomographic dataset, the microstructural features, such as content, size distribution, shape, and spatial distribution of micropores inside the cell wall, were determined. Together with a dual energy imaging technique, the 3D distribution of Zn in the alloyed foam was assessed by the subtraction of two images acquired above and below the Zn K‐absorption edge. The damage behavior of the alloyed foam was also clarified by this element sensitive imaging technique.